10 minute guide to beating debt - Abentrod, Susan (10 minute guides, 1996)
The 10 Minute Guide to Beating Debt is your first step to achieving financial security. Each easy-to-understand 10 minute lesson is full of strategies to help you spend less, save more, and reduce your credit card bills. This book is the complete guide to getting, using, and managing debt wisely even if you're a credit card junkie. 10 minutes is all you need to learn how to: Create a reasonable budget that you'll be able to follow Find credit cards with lower fees and no fees Review your outstanding loans and see whether you can speed up repayments Manage your own credit problems or determine whether you should consult a professional for help Re-establish credit after you have paid off all your debts.